2014
DOI: 10.1177/0973801014544580
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Vector Autoregression Model for Monetary Policy Analysis in India

Abstract: A structural vector autoregression (SVAR) model is proposed for analysing the impact of monetary policy stances on real variables in the Indian economy, in the context of its continuous exposure to global factors like oil price shocks and changes in global financial health. The empirical findings based on monthly data relating to the post-liberalisation period (April 1992-December 2012 suggest that contractionary monetary policy has had a considerable adverse impact on output for a year, which appears to be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Based on monthly data from 1993:1 to 2009:9, Sharma et al (2010) have found that money supply causes output in the short run, while in the long run it only affects prices. Pramanik and Kamaiah (2014) have found that contractionary monetary policy has an adverse impact on Indian output from April 1992 to December 2012. Besides, they have also reported that an appreciation of the exchange rate negatively impacts industrial production but causes an increase in price level.…”
Section: The Effectiveness Of Monetary Policy: a Review Of Empirical mentioning
confidence: 99%
“…Based on monthly data from 1993:1 to 2009:9, Sharma et al (2010) have found that money supply causes output in the short run, while in the long run it only affects prices. Pramanik and Kamaiah (2014) have found that contractionary monetary policy has an adverse impact on Indian output from April 1992 to December 2012. Besides, they have also reported that an appreciation of the exchange rate negatively impacts industrial production but causes an increase in price level.…”
Section: The Effectiveness Of Monetary Policy: a Review Of Empirical mentioning
confidence: 99%
“…Following [48,69,70], the process of generating the IRFs and VEDs is to re-specify the auto regressive function as follows:…”
Section: Derivation Of Variance Decomposition and Impulse Response Fu...mentioning
confidence: 99%
“…There have been attempts to study the relationship between these variables in the Indian economy; see, for example, Sabade (2014), Paramanik and Kamaiah (2014), Rami (2010), Ramachandran (2004) and Das (2010). This article is a contribution to the literature.…”
Section: Introductionmentioning
confidence: 99%